Ultra-dense networks principles and applications - Zhang, Haijun ca. 20./21. Jh; Lee, Jemin 1981-; Quek, Tony Q. S. 1973-; I, Chih-Lin ca. 20./21. Jh (Cambridge University Press, 2020)
Understand the theoretical principles, key technologies and applications of UDNs with this authoritative survey. Theory is explained in a clear, step-by-step manner, and recent advances and open research challenges in UDN physical layer design, resource allocation and network management are described, with examples, in the context of B5G and 6G standardization. Topics covered include NOMA-based physical layer design, physical layer security. Interference management, 3D base station deployment, software defined UDNs, wireless edge caching in UDNs, UDN-based UAVs and field trials and tests. A perfect resource for graduate students, researchers and professionals who need to get up to speed on the state of the art and future opportunities in UDNs